2012
DOI: 10.1186/1472-6882-12-55
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Korean standard pattern identification for stroke (K-SPI-Stroke) questionnaire

Abstract: BackgroundThe present study was conducted to examine the reliability and validity of the ‘Korean Standard Pattern Identification for Stroke (K-SPI-Stroke)’, which was developed and evaluated within the context of traditional Korean medicine (TKM).MethodsBetween September 2006 and December 2010, 2,905 patients from 11 Korean medical hospitals were asked to complete the K-SPI-Stroke questionnaire as a part of project ' Fundamental study for the standardization and objectification of pattern identification in tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Two of these SNPs are located in the UCP-1 promoter region, and the other SNP is located in exon 2. All of the studied SNPs satisfied the Hardy-Weinberg equilibrium (p > 0.05) according to the International HapMap Project [17]. The LD coefficients between the 3 SNPs are shown in Figure 1(B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these SNPs are located in the UCP-1 promoter region, and the other SNP is located in exon 2. All of the studied SNPs satisfied the Hardy-Weinberg equilibrium (p > 0.05) according to the International HapMap Project [17]. The LD coefficients between the 3 SNPs are shown in Figure 1(B).…”
Section: Resultsmentioning
confidence: 99%
“…In order to minimize the regional bias, the subjects were recruited from 10 Oriental Medical Hospitals from 2006 to 2010, including from Kyung-Hee Oriental Medical Hospital (Houeugi, Koduk in Seoul), Dae-Jeon University Oriental Medical Hospital, Wonk-Kang Oriental Medical Hospital (Jeonju, Iksan), Dong-Guk Oriental Medical Hospital (Ilsan), Kyung-Won Oriental Medical Hospital (Seoul), Dong-Sin Oriental Medical Hospital (Kwangju, Sunchon), and Sang-Ji Oriental Medical Hospital. The classification on 583 DP and 1,010 non-DP group (FH, QD, YD and BS) was performed by two TKM doctors using the Standard Pattern Identification for Stroke (K-SPI-Stroke) [17]. Patients participated in this study were diagnosed as cerebral infarction by computed tomography or magnetic resonance imaging.…”
Section: Methodsmentioning
confidence: 99%
“…These complexities of sign and symptoms complicate PI diagnosis and may cause diagnostic error between TKM doctors. Previous studies reported that concordance rates between two expert TKM doctors about PI diagnosis for stroke, pulse, or tongue diagnosis were 70–90%, which means that the diagnostic error may always be implied [29–31]. For these reasons, reliable biomarkers for more accurate diagnosis of PI are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have shown that it is possible to standardise and validate patterns using objective methods and evidence-based approaches [8][9][10][11][12][13][14]. Cluster analysis, a multivariate statistical method is commonly used to identify homogeneous subgroups and has been recognised as a suitable technique for identifying CM patterns of diseases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%